Being boys : youth, leisure and identity in the inter-war years - Tebbutt, Melanie (Gender in history., 2012)
This work offers a fresh and original approach to the masculinities, subjectivities and emotions of adolescence by exploring the leisure lives of working-class boys and young men in the inter-war years.